Bridging the gap – a new role for STAT3 in TLR4-mediated metabolic reprogramming - O'Neill, Luke (My University, 2021)
In this article, we discuss a new study from the laboratory of Ashley Mansell that successfully links innate immune receptor signaling to metabolic changes in macrophages, establishing for the ﬁrst time an uninterrupted pathway from ligand binding to mitochondrial reprogramming and subsequential effector function modulation in this cell type.
Keywords: ligand binding; macrophages; ligand binding; macrophages